2015
DOI: 10.1111/jocs.12610
|View full text |Cite
|
Sign up to set email alerts
|

Heart Transplantation With Pulmonary Vein Reconstruction in Ewing's Sarcoma in the Right Ventricular Outflow Tract

Abstract: Ewing's sarcoma is a histological type of malignant mesenchymal tumor and rarely originates from the heart. We report a case of Ewing's sarcoma located in the right ventricular outflow tract that invaded the left pulmonary vein in a 29-year-old female.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Only one patient received radiotherapy along with pre- and post-surgical chemotherapy. 14 Of 11 other cases, 5 of them had just tumor resection, 15–19 3 had tumor resection with both chemotherapy and radiotherapy, 2022 2 of them had cardiac transplantation, 23,24 and 1 had tumor resection with chemotherapy. 25…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one patient received radiotherapy along with pre- and post-surgical chemotherapy. 14 Of 11 other cases, 5 of them had just tumor resection, 15–19 3 had tumor resection with both chemotherapy and radiotherapy, 2022 2 of them had cardiac transplantation, 23,24 and 1 had tumor resection with chemotherapy. 25…”
Section: Resultsmentioning
confidence: 99%
“…Only one patient received radiotherapy along with pre-and post-surgical chemotherapy. 14 Of 11 other cases, 5 of them had just tumor resection, [15][16][17][18][19] 3 had tumor resection with both chemotherapy and radiotherapy, [20][21][22] 2 of them had cardiac transplantation, 23,24 and 1 had tumor resection with chemotherapy. 25 In follow-up of different durations from the beginning to a maximum of 30 months, 53% of patients were alive (n = 9); three had no evidence of disease after 24 months (NED = 24), two had NED = 12, and four of them with NED = 30,86,2 months.…”
Section: Primary Pnetmentioning
confidence: 99%
“…Among the primary cardiac sarcomas, Ewing’s sarcoma is quite rare. To our knowledge, only a few reports have described primary cardiac Ewing’s sarcoma [1, 2] and no reports have described primary Ewing’s sarcoma of the RA wall.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are 2 reported cases in which upfront chemotherapy was administered in adult patients before surgical resection and cardiac transplantation, with long-term good prognosis. 8,11 Previous cooperative studies reported a clinical benefit from high-dose chemotherapy for patients with ES and high-risk factors. 20 The use of radiotherapy as adjuvant therapy needs to be evaluated on a case-to-case basis, as the potential benefits from radiotherapy have to be balanced versus long-term toxicities: when necessary, as in our case, the patient and his family need to be informed about the potential life-threatening morbidities, such as nonreversible restrictive cardiomyopathy and myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Cho et al 11 described for the first time a heart transplantation with pulmonary vein reconstruction in adult EES of the right ventricular outflow tract, after an upfront chemotherapeutic course.…”
Section: Discussionmentioning
confidence: 99%